True identity of Avrainvillea and Rhipilia (Bryopsidales, Chlorophyta) from the Coast of Bahia, Brazil - Do Nascimento Santos, Gabriel; de Castro Nunes, José Marcos (Phytotaxa, 2015)
The coast of Bahia is the most extensive coastline in Brazil. There is great diversity in its coastal environments and these are considered to be a priority area for floristic surveys. Although representative species of the Avrainvillea and Rhipilia (Bryopsidales, Chlorophyta) genera are common in tropical and temperate marine habitats where they form an important component of the flora, most studies of their diversity in Bahia are of a floristic nature. The biology and ecology of these genera are still poorly understood and, for this reason, many taxa may have been incorrectly identified. This study aimed to perform a taxonomic analysis of Avrainvillea and Rhipilia genera from the coast of Bahia State, Brazil. Specimens used for the study were from samples collected between 1964 and 2013, deposited in the main Brazilian herbaria, to which visits and/or loan requests were made. Five infrageneric taxa, distributed in both genera, were identified as Avrainvillea (3) and Rhipilia (2). Identification keys, descriptions, and comparisons to related taxa are showed.